2015
DOI: 10.1080/15592294.2014.1003747
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductor-based sequencing of genome-wide DNA methylation states

Abstract: Methylated DNA immunoprecipitation sequencing (MeDIP-Seq) is a widely used approach to study DNA methylation genome-wide. Here, we developed a MeDIP-Seq protocol compatible with the Ion Torrent semiconductor-based sequencing platform that is low cost, rapid, and scalable. We applied this protocol to demonstrate MeDIP-Seq on the Ion Torrent platform provides adequate coverage of CpG cytosines, the methylation states of which we validated at single-base resolution on the Infinium HumanMethylation450 BeadChip arr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…However, genome-wide studies have revealed that DNA methylation within gene bodies is far more frequent than at promoters (5, 5961), playing a role in tissue-specific alternative promoter usage (5). Preferential positioning of DNA methylation over exons compared with introns (6265) prompted speculation for its potential role in pre-mRNA splicing, which has been confirmed by further studies (6, 66, 67). Interestingly, readers of DNA methylation including MeCP2 and methylation-sensitive proteins such as CTCF play roles in exon recognition and alternative splicing (6, 66).…”
Section: Role Of 5-hmc In Demethylationmentioning
confidence: 88%
See 2 more Smart Citations
“…However, genome-wide studies have revealed that DNA methylation within gene bodies is far more frequent than at promoters (5, 5961), playing a role in tissue-specific alternative promoter usage (5). Preferential positioning of DNA methylation over exons compared with introns (6265) prompted speculation for its potential role in pre-mRNA splicing, which has been confirmed by further studies (6, 66, 67). Interestingly, readers of DNA methylation including MeCP2 and methylation-sensitive proteins such as CTCF play roles in exon recognition and alternative splicing (6, 66).…”
Section: Role Of 5-hmc In Demethylationmentioning
confidence: 88%
“…As has been described for 5-mC (6), such exonic patterns of 5-hmC appears to be a common observation (84, 85) and suggest it may play a role in pre-mRNA splicing. In contrast to 5-mC where depletion is typically observed (5, 29, 67), 5-hmC appears significantly enriched at TES regions (67, 8183) (Figure 2). Although the functional role of 5-hmC at TES has not been explicitly examined, integrating this distribution with studies of RNA revealing tissue-specific transcription initiation near TES (88, 89) and novel post-transcriptional RNA methylation at 3′-UTRs (90) implicate additional roles for 5-hmC in transcription and RNA methylation, respectively.…”
Section: Genomic Localization Of 5-hmc and Potential Functional Rolesmentioning
confidence: 95%
See 1 more Smart Citation
“…Epigenomics is the study of heritable gene regulation that does not involve the DNA nucleotide coding sequence itself but acts on a genome-wide scale via DNA nucleotide methylation and posttranslational modifications of histones, the interaction between transcription factors and their targets, and nucleosome positioning [23][24][25][26][27][28][29][30]. Methylomics is the genome-wide analysis of DNA methylations and their effects on gene expression and heredity [28].…”
Section: Methylomics and Epigenomicsmentioning
confidence: 99%
“…However, WGS may be preferred over WES because it provides more data with better uniformity of read coverage on disease-associated variants and reveals polymorphisms outside coding regions and genomic rearrangements [19,22]. The analysis of the methylome by MeS complements WGS, WES, and CGS to determine the active methylation sites and the epigenetic markers that regulate gene expression, epistructural base variations, imprinting, development, differentiation, disease, and the epigenetic state [23][24][25][26][27][28][29][30]. The impact of NGS technology is indeed egalitarian in that it allows both small and large research groups the possibility to provide answers and solutions to many different problems and questions in the fields of genetics and biology, including those in medicine, agriculture, forensic science, virology, microbiology, and marine and plant biology.…”
Section: Introductionmentioning
confidence: 99%